Implementasi Artificial Intelligence (AI) Menggunakan Canva Dalam Pengembangan Powerpoint Interaktif Sebagai Medi Pembelajaran IPAS Di Sekolah Dasar - Estuhono, Estuhono; Safitri, Nadya (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This research is motivated by difficulties students face in understanding IPAS learning. This is because the teaching materials used are still in the form of printed media, while the facilities and infrastructure are very limited, and even students are very enthusiastic about digital learning. Therefore, this has impact on student’s learning outcomes. The aim if thus research is to produce interactive PowerPoint using canva as a learning medium for IPAS in a valid, practical, and effective manner. The research methoud used is the research and development (R&D) method. The learning model used is the ADDIE model, consisting if five stage: Analyze (analysus), design, development, implementation, and evaluation. The type of data collected is qualitative and quantitative data. Data collection techniques used in this research are interviews, observations, and questionnaires. The results of the validation of the interactive PowerPoint for IPAS subjects in fourth grade, validated by three validators, obtained a score of 80,55% categorized as valid. The practicality result assessed from students’ responses obtained a score of 78,3% categorized as practical. Based on this analysis, it is concluded that the interactive PowerPoint using the canva application is declared practical. Furthermore, the effectiveness was assessed, and students’ learning outcomes obtained an average score of 83,52% categorized as very effective.